AKIBAT HUKUM ATAS PENENTUAN HARGA TRANSFER ANTAR NEGARA (TRANSFER PRICING) YANG TIDAK WAJAR PADA PERSEROAN TERBATAS - Lesley Lesley; Bismar Nasution; Bastari Bastari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Tax is one of the biggest income for implementing development. In reality, however, many business people attempt to avoid tax by doing many wrong ways, and one of them is by doing unreasonable transfer pricing among them who have special relation such as transaction on multinational limited liability companies. The research used juridicial normative method which analyzed secondary data obtained from primary, secondary, and tertiary legal materials. The whole data were gathered by conducting library research method and analyzed qualitatively. Transfer pricing is under pricing and over pricing in which when it is not done according to reasonable price, it is the practise for avoiding tax. Legal remedy in fiscus toward this practise is by using Advance Pricing Agreement (APA) and tax audit in which legal product which can be issued is SKPKB (unpaid tax certificate) as one of the causes of dispute in tax due to the disagrement between fiscus and taxpayers. Legal remedy can be filed upon the SKPKB to the Tax Court. Legal remedy for the decision can be filed to the court of appeals, and if the verdict does not satisfy the taxpayer, he can file judiciala review. When the Court states that the taxpayers are required to pay the unpaid tax as it is specified in the SKPKB, and when taxpayers do not pay in due time, DJP can do its duty to do tax collection. When the whole assets of the limited liability company are inadequate to pay the tax, DJP can collect the tax of the personal property of the persons in charge of the company such as directors, commissioners, and shareholders.